Compressive Strength and Water Absorption Analysis of Perforated Paving Blocks Incorporating Waste Candlenut Shell Ash - Aprilia Sari, Nur Fajar; Cahyono, Luqman; Rismawati, Ria; Sholihah, Mar'atus (Fakultas Teknik Universitas Tanjungpura, 2026)
The extensive use of candlenut shells as boiler fuel generates substantial ash residues that pose environmental challenges if inadequately managed. Concurrently, conventional paving blocks exhibit limited permeability, thereby increasing urban surface runoff. This study evaluates the feasibility of incorporating candlenut shell ash as a partial replacement for fine aggregate in perforated paving blocks. Distinct from prior studies that focus on ash application in dense concrete systems, this research emphasizes permeability-oriented pavement performance alongside material valorization. Chemical composition was determined using X-ray Fluorescence analysis, while mechanical and durability-related properties, including compressive strength and water absorption, were assessed in accordance with SNI 03-0691-1996. The ash contained 80.04% CaO, suggesting potential pozzolanic activity. Experimental results indicate that a 1:4 mix proportion provides optimal performance, achieving a compressive strength of 20.60 MPa that satisfies Quality B requirements and a water absorption of 9%, meeting Quality C criteria. These findings demonstrate the technical viability of candlenut shell ash for permeable paving applications and support its integration into sustainable urban drainage and circular material management systems.